Yoga and music intervention reduces inattention, hyperactivity/impulsivity, and oppositional defiant disorder in children’s consumer with comorbid ADHD and ODD - Luo, Xue; Huang, Xu; Lin, Shuang (Frontiers in Psychology, 2023)
This preliminary study used a randomized controlled design to investigate whether a 16-week combined yoga and music intervention improves attention, hyperactivity/impulsivity, and oppositional defiant disorder (ODD) in 60 children with attention-deficit/hyperactivity disorder (ADHD) comorbid with ODD aged 4–6 years. It also preliminarily identified which intervention is best for these children among three types: combined yoga and music, yoga-only, and music-only interventions. We used both the parent- and teacher-rated MTA SNAP-IV ADHD Rating Scale for data collection. We found that the combined yoga and music intervention had a positive effect on inattention, hyperactivity/impulsivity, and ODD in children with comorbid ADHD and ODD. The combined yoga and music intervention was the most effective in reducing inattention (η^2in repeated measures ANOVA effect size, 0.9; followed by the yoga- and the music-only interventions, respectively), hyperactivity/impulsivity (effect size, 0.92), and ODD behaviors (effect size, 0.93) in children with comorbid ADHD and ODD. Thus, the combined yoga and music intervention was the most effective and had a more comprehensive effect on children with combined ADHD and ODD compared with the two other interventions (i.e., yoga- and music-only interventions). Our findings provide preliminary evidence for the use of combined yoga and music interventions on a daily basis as a safe and effective adjunctive treatment for children with comorbid ADHD and ODD.